(untitled) (Contemporary Journal of Social Science Review, 2025)
The question of interfaith harmony has become increasingly significant in today’s globalized yet fragmented world. Islam, like other major religions, emphasizes universal values of peace, justice, compassion, and human dignity, which provide a common ground for dialogue with followers of other faith traditions. The Qur’an advocates engagement with Ahl al-Kitāb (People of the Book) on the basis of common beliefs (Q. 3:64).[1] Classical Muslim scholars such as al-Ghazālī and Ibn Taymiyyah emphasized justice, ethical conduct, and coexistence as essential to social order.[2] In modern scholarship, Hans Küng’s Global Ethic project and Karen Armstrong’s writings on compassion have highlighted the necessity of shared values for peaceful coexistence. [3]Despite these convergences, contemporary societies continue to face sectarianism, religious prejudice, and identity-based conflicts, raising the problem of how commonalities can be mobilized to counter intolerance. This study employs a comparative and analytical methodology. It examines scriptural teachings, ethical frameworks, and historical precedents from Islam alongside those of Christianity, Judaism, and other world religions. Primary sources, such as the Qur’an and Hadith, are analyzed in dialogue with Biblical and Rabbinic texts, while secondary literature—including the works of Wilfred Cantwell Smith, Sayed Hossein Nasr, and Charles Kimball—is critically reviewed.[4]By integrating theological analysis with sociological perspectives, the research highlights religious and social intersections that can serve as pathways to harmony. The significance of this study lies in its contribution to the academic fields of comparative religion, Islamic studies, and peacebuilding. At a time when global conflicts are often framed in religious terms, identifying and promoting shared values offers practical strategies for reducing tensions and fostering interfaith [1] Al-Imran, 3:64. [2] Abu Ḥāmid al-Ghazālī, Iḥyāʾ ʿUlūm al-Dīn (Cairo: Dār al-Maʿrifa, n.d.); Ibn Taymiyyah, Al-Jawāb al-Ṣaḥīḥ li-man baddala dīn al-Masīḥ (Riyadh: Dār al-ʿĀṣima, 1993). [3] Hans Küng, Global Responsibility: In Search of a New World Ethic (New York: Crossroad, 1991); Karen Armstrong, Twelve Steps to a Compassionate Life (New York: Alfred A. Knopf, 2010). [4] Wilfred Cantwell Smith, The Meaning and End of Religion (Minneapolis: Fortress Press, 1991); Sayed Hossein Nasr, The Heart of Islam: Enduring Values for Humanity (San Francisco: Harper San Francisco, 2002); Charles Kimball, When Religion Becomes Evil (San Francisco: Harper San Francisco, 2002). dialogue. For researchers and academicians, this work provides both a theoretical framework and practical implications for curriculum development, dialogue initiatives, and policy-making in pluralistic societies.